An analysis of two regional versions of a social accounting matrix in Spain: Catalunya vs. Andalusia - Manuel Alejandro Cardenete; Emilio Congregado; Ignacio Pomares (European Regional Science Association (ERSA), 1998)
The goal of this paper is to compare a reduced version of a social accounting matrix (SAM) for Andalusia and Catalunya. Using available data for Regional Accounts, Input-output tables, etc., we provide a complete picture of flow among economic agents (four producers, one consumer, the Government and one foreing agent). It is obvions this is a preliminary paper because for its usage we must avoid some statistic mistakes observed in our regional statistics nowdays, this chore we left for future workings. The SAM may be userful to the Regional Agencies in charge of constructing the Regional Accounts, as well as researchers in appiled general equilibrium. We want to present the structural differences between these regions by mean of multivariate analysis, using as data their respectives SAM (I beg your perdon for our delayed)
Keywords: 330